Remoção de cor de corantes de efluentes sintético e real em sistemas anaeróbios de um e dois estágios suplementados ou não com doador de elétrons e mediador redox - Firmino, Paulo Igor Milen (2009)
The release of textile effluents into superficial water bodies represents a serious environmental problem and a public health concern because lots of dyes from wastewater and their breakdown products are potentially toxic and carcinogenic. Colour removal of dyes is still a challenge for textile industry wastewater treatment plants. Amongst the decolourisation methods, the anaerobic treatment has called attention for being economically attractive. This work reports two textile wastewater colour removal experiments. The first one aimed, primarily, to assess and compare colour removal of synthetic textile effluent, which contained the azo dye Congo Red (CR), in an one-stage anaerobic system, consisted of only a UASB reactor (R1), and in a two-stage anaerobic system (R2), consisted of an acidogenic (R2,A) followed by a methanogenic reactor (R2,M). The reactors were run under different operational conditions by varying the initial dye and electron donor (ethanol) concentrations as well as the hydraulic retention time (HRT) of the reactors. It was observed that, with gradual increase of CR concentration from 0.3 to 1.2 mM, R1 total average colour removal efficiency decreased from 97.8 to 95.1%, while R2 did not present remarkable variation, and R2,A was responsible for the major part of total decolourisation reached (98.5%). Concerning the initial ethanol concentration, a less than 2% drop was observed at R1 average efficiency against an almost 6% one at R2 by reducing the substrate concentration from 1.0 to only 0.2 g COD/L. And, by reducing the systems total HRT from 24 for 12 hours, the R1 and R2 average efficiencies changed from, approximately, 98% to 96.6 and 97.7%, respectively. Afterwards, those same systems were fed with real textile wastewater, and, although both have presented lower colour removal efficiencies than the ones achieved with CR, R1 reached a 7% average value higher than R2. The second experiment aimed to assess and compare the real textile wastewater colour removal in one-stage anaerobic systems (HRT = 12 h) supplemented or not with electron donor (ethanol) and redox mediator (AQDS). No difference was observed between decolourisation efficiency average values achieved by the reactor supplemented with AQDS (R3) and by the reactor free of this compound (R4). However, in the absence of ethanol, both reactors have presented lower colour removal efficiency values, the R3 reached a 5% average efficiency higher than R4 one. It can be concluded that the used anaerobic systems achieved good decolourisation efficiencies with both synthetic and real textile wastewaters under the different operational conditions studied. The redox mediator impact was not evident in the treatment of the real effluent at HRT of 12 hours, and the absence of an external electron donor reduced the reactors colour removal efficiency